Answer:
infinite solutions
Step-by-step explanation:
Given
- 6(n - 8) = 4(12 - 5n) + 14n ← distribute parenthesis on both sides
- 6n + 48 = 48 - 20n + 14n, that is
- 6n + 48 = 48 - 6n ( add 6n to both sides )
48 = 48 ← True
This indicates that the equation is true for any value of n
Answer:
This is a very classical type of equation in which, the solution is basically any number and it is known as an "Identity". So it has infinite solutions
Step-by-step explanation:
Apply the distributive law to both sides of the equation:-6(n-8) = 4(12-5n)+14n
-6n-6*(-8) = 4*12+4*(-5n) + 14n
Reduce similar terms-6n+48=48-20n+14n
-6n+48=48-6n
From here it is clear them to see that by adding -48 and 6n to both sides one obtains the identity 0 = 0-6n+48=48-6n
-6n +6n + 48 -48 = 48 -48 - 6n + 6n
0 = 0
So every time you find this kind of problem and after reducen the equation you end up with a true statement, then the equation has infinite solutionsDiego moves the shape down, turns it 90 degrees clockwise, then moves the shape to the right. Draw the location of the shape after each move.HELP!!!
The shape moves from its original position, point A, to a point down from A, point B, after the first move. Even after a 90-degree clockwise rotation, because we are considering the shape as a point, it will still be at point B. The final move to the right places the shape at point C. The final position of the shape is at point C.
Explanation:For the purpose of illustrating this problem, let's assume that the original placement of the shape is at point A. Now, based on the movements described, here are the steps:
Move the shape down: This results in a downward shift from point A, let's say to point B. Turn it 90 degrees clockwise: The direction of a shape after a 90-degree clockwise rotation changes, but if we consider the shape as a simple point, its location would still be at point B. Move the shape to the right: From point B, if we move the shape rightwards, it will now be at a new location, let's say point C.
The final location of the shape will be at point C, which is down and to the right of the initial position, point A, after a clockwise rotation.
Learn more about Spatial Movement here:https://brainly.com/question/34447957
#SPJ2
Peppers are priced 3 for $1.02 . How much would one pepper cost
Answer:
0.34 cents
Step-by-step explanation:
You simply divide 1.02 by the 3 peppers.
How do you calculate 2 5/6
What is 5 divided by 3/7
Final answer:
To divide 5 by 3/7, we multiply 5 by the reciprocal of 3/7 which is 7/3, resulting in 35/3 or 11 2/3.
Explanation:
To calculate 5 divided by 3/7, we invert the fraction 3/7 and multiply by 5. It’s the same as multiplying 5 by the reciprocal of 3/7. The reciprocal of 3/7 is 7/3. Therefore:
5 × 7/3 = 5 × (7 ÷ 3)
5 × 7/3 = (5 × 7) ÷ 3
5 × 7/3 = 35/3
5 × 7/3 is 11 with 2 left over or, in other words, it is 11 2/3.
Remember, when you divide by a fraction, you are essentially calculating how many times that fraction goes into the number. So here, 5 divided by 3/7 is asking how many groups of 3/7 there are in 5, which is why we multiply by the reciprocal.
Label each angle as acute, obtuse, right, or straight and estimate the measure in degrees.
Answer:
7) Obtuse, I didn't use a protractor, so I'm estimating about 130 degrees.
8) Straight, all straight lines are equal to 180 degrees.
9) Acute, I estimated about 30-40 degrees, again, no protractor used.
Step-by-step explanation:
What is an equation of the line that passes through the point (-2,3) and is parallel to the line whose equation is y=3/2x-4?
Answer:
Step-by-step explanation:
We can model a line with slope-intercept form:
[tex]y = mx + b[/tex]
where [tex]m[/tex] is the slope and [tex]b[/tex] is the Y-intercept.
We know that the new line is parallel to the given line, so the two lines have the same slope, or [tex]m = \frac{3}{2}[/tex]:
[tex]y = \frac{3}{2}x + b[/tex]
To determine [tex]b[/tex], we just need to plug in the given point that the line passes through, [tex](-2, 3)[/tex]:
[tex]y = \frac{3}{2}x + b[/tex]
[tex](3) = \frac{3}{2}(-2) + b[/tex]
[tex]3 = -3 + b[/tex]
[tex]b = 6[/tex]
This gives us the following equation:
[tex]y = \frac{3}{2}x + 6[/tex]
The equation of the line is y = (3/2)x + 6.
What is an equation of a line?The equation of a line is given by:
y = mx + c
where m is the slope of the line and c is the y-intercept.
Example:
The slope of the line y = 2x + 3 is 2.
The slope of a line that passes through (1, 2) and (2, 3) is 1.
We have,
The equation of the line passes through the point (-2,3).
y = m(1)x + c
The equation of the line is parallel to the line whose equation is y=3/2x-4.
This means,
y = (3/2)x - 4
This is in the form of y = m(2)x + c
m(2) = (3/2)
So,
m(1) = m(2)
Now,
(-2, 3) = (x, y)
y = m(1)x + c
3 = (3/2) x (-2) + c
3 = -3 + c
c = 3 + 3
c = 6
Now,
y = m(1)x + c
y = (3/2)x + 6
Thus,
The equation of the line is y = (3/2)x + 6.
Learn more about equation of a line here:
https://brainly.com/question/23087740
#SPJ6
a taxi charges $1.75 for the first 1/8 mile and $0.30 for each additional 1/8 mile write an equation that gives the cost c of a taxi ride in terms of the number of miles m how many miles did you drive if a ride cost $7.75
The cost of a taxi ride can be calculated using the equation c = 1.75 + (m - 1/8) * 8 * 0.30, where c represents the total cost and m represents the total miles driven. Solving this equation for m when the total cost is $7.75 would yield the number of miles driven.
Explanation:The subject of this question is the creation of an equation to calculate the cost of a taxi ride. According to the question, a taxi charges $1.75 for the first 1/8 mile and $0.30 for each additional 1/8 mile. First, we need to convert miles to 1/8 miles, since the pricing is based on this fraction. We know that each full mile is equal to 8 fractions of 1/8 mile. Therefore, to convert miles to 1/8 miles, we multiply the number of miles by 8.
Given this pricing structure, the costs associated with additional miles driven beyond the first 1/8 mile (which are already accounted for by the initial $1.75), can be represented by (m-1/8)*8*0.30. Here, (m-1/8) represents the additional miles traveled beyond the first 1/8 mile, and multiplying this by 8 converts these miles into 1/8 miles.
The total cost, c, can thus be represented by the equation c = 1.75 + (m - 1/8) * 8 * 0.30. If a ride cost $7.75, we can substitute this cost into the equation and solve for m to find the number of miles driven. This would give us the equation: 7.75 = 1.75 + (m - 1/8) * 8 * 0.30.
Learn more about Algebra here:https://brainly.com/question/32436021
#SPJ2
The sun produces 3.9 * 10^33 ergs of radiant energy per second. How many ergs of radiant energy does the sun produce in 3.25 * 10^3 seconds?
Answer: [tex]1.2675*10^{37}\ ergs[/tex]
Step-by-step explanation:
Let be "x" the amount of ergs the sun produces in[tex]3.25 * 10^3\ seconds[/tex].
According to the information provided in the exercise, in 1 second the sun produces [tex]3.9 * 10^{33}\ ergs[/tex] of radiant energy.
Then, in order to find the value of "x" you can write the following proportion:
[tex]\frac{ 3.9 * 10^{33}\ ergs}{1\ second}=\frac{x}{3.25 * 10^3\ seconds}[/tex]
Finally, you must solve for "x".
Therefore, you get:
[tex]x=\frac{( 3.9 * 10^{33}\ ergs)( 3.25 * 10^3 seconds)}{1\ second}\\\\x=1.2675*10^{37}\ ergs[/tex]
4m – 5n + 6p + 2m - 3n – 2p
What is the slope of the line that passes through the points (−3,1) and (7,−14)? Write your answer in simplest form.
Answer is provided in the image attached.
Using the slope formula, the slope, in simplest form, of the line that goes through (-3, 1) and (7, -14) is: [tex]\mathbf{-\frac{3}{2}}[/tex]
Recall:
Slope of a line that passes through any two points is found using the formula: [tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
Given the two points that the line passes through are: (-3, 1) and (7, -14)
Let,[tex](-3, 1) = (x_1, y_1)\\\\(7, -14) = (x_2, y_2)[/tex]
Substitute[tex]m = \frac{-14 - 1}{7 - (-3)} = \frac{-15}{10} \\\\m = -\frac{3}{2}[/tex]
Therefore, using the slope formula, the slope, in simplest form, of the line that goes through (-3, 1) and (7, -14) is: [tex]-\frac{3}{2}[/tex]
Learn more here:
https://brainly.com/question/15316550
A set of data has a mean of 45.6 what is the mean if 5.0 is added to each score
Answer:
The mean will be increased by 5
Step-by-step explanation:
Suppose a set of data [tex](2, 4, 6, 8, 10, 12)[/tex]
Mean is defined as sum of all the values given set of data divided by total number of values.
Mean1 = [tex]\frac{2+4+6+8+10+12}{6} = \frac{42}{6} = 7[/tex]
Now if we add 5 toeach value, the new set becomes [tex](7, 9, 11, 13, 15, 17)[/tex]
for which,
Mean2 = [tex]\frac{7+9+11+13+15+17}{6} = \frac{72}{6} = 12[/tex]
Mean2 - Mean1 = 5
Solve for g.
89 - 49 = 8
Help
An outdoor spa (hot tub) draws 1487 watts to keep the water warm. If the utility company charges $0.13 per kilowatt-hour, how much does it cost to operate the spa for four months during the winter (24 hours per day)? Assume each month has 30 days.
Answer:$556.73
Step-by-step explanation:
Watts (1487) multiplied by the hours used daily (24) =35688
Divided by 1000 = 35.68
multiply 35.68 times the number of days (120) = $556.73
Another example:
wattage x hours used ÷ 1000 x price per kWh = $$
1487 x 2880 ÷ 1000 x $0.13 = $556.73
Answer:
$556.7328 is total cost of operating hot tub for 4 months in an outdoor spa.
Step-by-step explanation:
Power drawn by hot tub = 1487 Watts = 1.487 kiloWatt
1 Watt = 0.001 kiloWatt
Utility charges charged by the company = $0.13 / (kiloWatt hour)
Charges in 1 day or 24 hours : (1 day = 24 hours)
$0.13 / (kiloWatt hour) × 1.487 kiloWatt × 24 hours = $4.63944
4 months = 4 × 30 = 120 days (1 month = 30 days)
Total charge for operating hot tub for 4 months or 120 days:
$4.63944 × 120 = $556.7328
The original price of a mountain bike was reduced by $125.
If p = the mountain bike's original price in dollars, which algebraic expression
represents the reduced price?
A. 125+ p
B. 125p
c. p-125
D. 125 - P
Select all answers that have a value of 22?? Help..
Let's plug in the variables one by one.
6g - 2h
plug in 5 for g and 4 for h
6(5) - 2(4)
multiply
30 - 8
subtract
→ 22
20g
plug in 2 for g
20(2)
multiply
40
2(g + 1)
plug in 10 for g
2(10 + 1)
add
2(11)
multiply
→ 22
4g + 5h
plug in 1 for g and 4 for h
4(1) + 5(4)
multiply
4 + 20
add
24
Therefore, the answers that have a value of 22 are 6g - 2h and 2(g + 1)
Answer: 6g-2h when g=5 and h=4
and 2(g+1) when g=10 .
Step-by-step explanation:
1) 6g-2h
when g=5 and h=4, then we have
6(5)-2(4)=30-8=22
2) 20 g when g=2, we have
20(2)=40 ≠22
3) 2(g+1) when g=10 , we have
2(10+1)=2(11)=22
4) 4g+5h when g=1 and h=4, we have
4(1)+5(4)=4+20=21≠22
Hence, the required answer is : 6g-2h when g=5 and h=4
and 2(g+1) when g=10 .
What is the equation of the following line (4,-3) (0,0)
Answer:
y=5/4x
Step-by-step explanation:
Some wire is used to make 3 rectangles: A, B, and C. Rectangle B’s dimensions are 3/5 cm larger than Rectangle A’s dimensions, and Rectangle C’s dimensions are 3/5 cm larger than Rectangle B’s dimensions. Rectangle A is 2 cm by 3 1/5 cm.
a. What is the total area of all three rectangles?
b. If a 40-cm coil of wire was used to form the rectangles, how much wire is left?
Answer:
a. [tex]30.36\ cm^2[/tex]
b. [tex]1.6\ cm[/tex]
Step-by-step explanation:
a. You know that the dimensions of Rectangle A are [tex]2\ cm* 3\frac{1}{5}\ cm=2\ cm* 3.2 cm[/tex]
Since Rectangle B’s dimensions are [tex]\frac{3}{5}\ cm[/tex] (which is 0.6 cm) larger than Rectangle A’s dimensions, then the dimensions of Rectangle B are:
[tex](2\ cm+0.6\ cm)( 3.2\ cm+0.6\ cm)=2.6\ cm*3.8\ cm[/tex]
Since Rectangle C’s dimensions are [tex]\frac{3}{5}\ cm[/tex] (which is 0.6 cm) larger than Rectangle B's dimensions, then the dimensions of Rectangle C are:
[tex](2.6\ cm+0.6\ cm)( 3.8\ cm+0.6\ cm)=3.2\ cm*4.4\ cm[/tex]
The find the total area of all three rectangles you must add the products obtained when you multiply their dimensions. Then:
[tex]A_t=(2\ cm* 3.2 cm)+(2.6\ cm*3.8\ cm)+(3.2\ cm*4.4\ cm)\\\\A_t=30.36\ cm^2[/tex]
b. The perimeter of a rectangle can be calculated with this formula:
[tex]P=2l+2w[/tex]
Where "l" is the lenght and "w" is the width.
Knowing the dimensions of each rectangleg, you can calculate the total perimeter as follows:
[tex]P_t=(2)[(2\ cm+ 3.2 cm)+(2.6\ cm+3.8\ cm)+(3.2\ cm+4.4\ cm)]\\\\P_t=38.4\ cm[/tex]
Then, if a 40-cm coil of wire was used to form the rectangles, the amount of wire that is left is:
[tex]40\ cm-38.4\ cm=1.6\ cm[/tex]
-5|x+3|+3=-17 what’s the answer
Answer:
x=−7,1
Step-by-step explanation:
1 Subtract 33 from both sides.
-5|x+3|=-17-3−5∣x+3∣=−17−3
2 Simplify -17-3−17−3 to -20−20.
-5|x+3|=-20−5∣x+3∣=−20
3 Divide both sides by -5−5.
|x+3|=\frac{-20}{-5}∣x+3∣=
−5
−20
4 Two negatives make a positive.
|x+3|=\frac{20}{5}∣x+3∣=
5
20
5 Simplify \frac{20}{5}
5
20
to 44.
|x+3|=4∣x+3∣=4
6 Break down the problem into these 2 equations.
x+3=4x+3=4
-(x+3)=4−(x+3)=4
7 Solve the 1st equation: x+3=4x+3=4.
x=1x=1
8 Solve the 2nd equation: -(x+3)=4−(x+3)=4.
x=-7x=−7
9 Collect all solutions.
x=-7,1x=−7,1
Draw a rectangle with six regions to expand (2x + 4) (3x2 + 5x + 7).
To expand (2x + 4) (3x^2 + 5x + 7), draw a rectangle with six regions, multiply the terms in each region and add them together. The final expanded form is 6x^3 + 22x^2 + 34x + 28.
To expand the polynomial expression (2x + 4) (3x2 + 5x + 7), we will use the rectangle (or area) method. This involves drawing a rectangle divided into six regions, each representing a product of a term from the first binomial and a term from the second trinomial.
First, draw a 2x3 rectangle, with the dimensions representing the two terms in the first binomial and the three terms in the second trinomial.
Label the length of the rectangle with the three terms from the second trinomial, 3x2, 5x, and 7.
Label the width of the rectangle with the two terms from the first binomial, 2x and 4.
Fill in each of the six regions by multiplying the term at the end of the row by the term at the top of the column. For example, the top-left region would be 2x multiplied by 3x2, giving 6x3.
Continue filling in the other five regions: 2x times 5x is 10x2, 2x times 7 is 14x, 4 times 3x2 is 12x2, 4 times 5x is 20x, and 4 times 7 is 28.
Combine like terms to get the final expanded form: 6x3 + 22x2 + 34x + 28.
If x = 4y + 21y and y = 14 + 5, what is 3x × 7? No need to show your work.
y = 19
x = 4(19) + 21(19) = 76 + 399 = 475
3(475) × 7
1425 × 7
9975 <--- answer.
Hope this helped!
Nate
Answer:
the answer is 39
Step-by-step explanation:
30 POINTS + BRAINLIEST! Please if you can, help! I'm on a timer!
Triangle PQR is transformed to triangle P'Q'R'. Triangle PQR has vertices P(4, 0), Q(0, −4), and R(−8, −4). Triangle P'Q'R' has vertices P'(1, 0), Q'(0, −1), and R'(−2, −1).
Plot triangles PQR and P'Q'R' on your own coordinate grid.
Part A: What is the scale factor of the dilation that transforms triangle PQR to triangle P'Q'R'? Explain your answer. (4 points)
Part B: Write the coordinates of triangle P"Q"R" obtained after P'Q'R' is reflected about the y-axis. (4 points)
Part C: Are the two triangles PQR and P''Q''R'' congruent? Explain your answer. (2 points)
(There is no image provided.)
See the attached picture for the answers:
Final answer:
The scale factor of the dilation that transforms triangle PQR to triangle P'Q'R' does not exist. The coordinates for the reflected triangle P''Q''R'' are P''(-1, 0), Q''(0, -1), and R''(2, -1). Triangle PQR and triangle P''Q''R'' are not congruent.
Explanation:
To find the scale factor of the dilation that transforms triangle PQR to triangle P'Q'R', we can compare the lengths of corresponding sides in the two triangles. The distance between P(4, 0) and P'(1, 0) is 3, the distance between Q(0, -4) and Q'(0, -1) is 3, and the distance between R(-8, -4) and R'(-2, -1) is 6.
Since the lengths of corresponding sides are not equal, the triangles are not similar and there is no scale factor that transforms triangle PQR to triangle P'Q'R'.
To reflect triangle P'Q'R' about the y-axis, we simply change the sign of the x-coordinate for each vertex. The coordinates for the reflected triangle P''Q''R'' are P''(-1, 0), Q''(0, -1), and R''(2, -1).
Triangle PQR and triangle P''Q''R'' are not congruent because their corresponding sides have different lengths.
Subtract using the number line.
−1 1/3−1/6
A number line ranging from negative two to two with an arrow on both ends and tick marks every one sixth
−1 5/6
−1 1/2
−1 1/6
1 1/2
Answer:
−1 1/2
Step-by-step explanation:
i took the test <3
The subtraction of the given expression by the number line is -3/2.
The given expression is:
[tex]-1 \dfrac{1}{3} - \dfrac{1}{6}[/tex]
The improper fraction of [tex]-1 \dfrac{1}{3} =- \dfrac{4}{3}[/tex]
So, the given expression can be written as:
[tex]-\dfrac{4}{3} - \dfrac{1}{6}[/tex]
Since LCM of (3, 6) = 2
[tex]-\dfrac{4}{3} - \dfrac{1}{6} =\dfrac{-2\times 4 - 1}{6}\\\\ -\dfrac{4}{3} - \dfrac{1}{6} = -\dfrac{9}{6}\\\\ -\dfrac{4}{3} - \dfrac{1}{6} = -\dfrac{3}{2}\\\\[/tex]
Now according to the number
This subtraction will be done, if we add 1/6 toward the left side of the number line.
Hence,
The subtraction:
[tex]-\dfrac{4}{3} - \dfrac{1}{6} = -\dfrac{3}{2}\\\\[/tex]
The procedure by number line is attached below.
To learn more about number line visit:
https://brainly.com/question/32029748
#SPJ3
Identify the equivalent of:
6x + 2y = 12
A. y = 3x + 6
B. y = -3x - 6
C. y = 3x - 6
D. y = -3x + 6
Answer:
D. y = -3x + 6.
Step-by-step explanation:
6x + 2y = 12
2y = -6x + 12 Divide through by 2:
y = -3x + 6.
Answer:
D. y = -3x + 6
Step-by-step explanation:
6x + 2y = 12
-6x - 6x
_____________
2y = -6x + 12
__ ________
2 2
[tex]y = -3x + 6[/tex]
I am joyous to assist you anytime.
Need help now please
Answer:
all work is shown and pictured
Which of the following equations correctly shows the relationship between the values of x and the values of y?
Answer~ A. y=3x-4
Explanation~ Look at the X column. Start with the first row, which is 5 in the x column and 11 in the y column. Looking back at the equation. As you can see, it has the same variables that are in the table. Replace the x with the 5 from the table.
*Remember to put the 5 in parenthesis; you must always do this when plugging in numbers into your equations*
If done correctly, your equation should now look like this:
y=3(5)-4
Following PEMDAS, the order you solve order of operations, you must first multiply, as Multiplication is before Subtraction. So, you must multiply the 5 and 3. 5×3=15, so, now your equation should look like:
y=15-4
Simply subtract 4 from 15, and you should get 11. Therefore,
y=11
Continue this process down through the table to double check your work.
I hope I helped! Sorry for the dang essay lol
In the diagram, GB = 2x + 3..
What is GB?
Group of answer choices
15 units
10 units
30 units
5 units
Answer:
GB is 15 units
Step-by-step explanation:
see the attached figure to better understand the problem
we know that
The Centroid is a point of triangle where all 3 medians intersect
In this problem point G is the centroid of the triangle FDE
FA, EB and DC are medians of the triangle FDE.
Remember that centroid divides the median in 2:1
FA is a is median so FG:GA=2:1.
Find the value of x
[tex]\frac{FG}{GA}=\frac{2}{1}\\\\\frac{5x}{x+9}=\frac{2}{1}\\\\5x=2x+18\\\\5x-2x=18\\\\3x=18\\\\x=6[/tex]
Find the value of GB
GB=2x+3
substitute the value of x
[tex]GB=2(6)+3=15\ units[/tex]
4 - t = 3(t-1) - 5
A 3
B 6
C no solution
D Identity
Answer:
A
Step-by-step explanation:
Given
4 - t = 3(t - 1) - 5 ← distribute and simplify right side
4 - t = 3t - 3 - 5
4 - t = 3t - 8 ( subtract 3t from both sides )
4 - 4t = - 8 ( subtract 4 from both sides )
- 4t = - 12 ( divide both sides by - 4 )
t = 3
Suppose the price of a certain item increases by 3.8% a total of 5 times, and then decreases by 1.4%
a total of 2 times. By what overall percent did the price increase?
Answer:
The price was increased by 17.15%
Step-by-step explanation:
step 1
we have that
[tex]100\%+3.8\%=103.8\%=103.8/100=1.038[/tex]
Let
x -----> the price of a certain item
we know that
If a price increases by 3.8% a total of 5 times
then
The new price will be equal to multiply the original price by 5 times 1.038
so
[tex]x(1.038)(1.038)(1.038)(1.038)(1.038)=x(1.038)^5[/tex]
step 2
we have that
[tex]100\%-1.4\%=98.6\%=98.6/100=0.986[/tex]
we know that
If a price decreases by 1.4% a total of 2 times
then
The new price will be equal to multiply the actual price by 2 times 0.986
The actual price is [tex]x(1.038)^5[/tex]
so
[tex]x(1.038)^5(0.986)(0.986)=x(1.038)^5(0.986)^2=1.1715x[/tex]
[tex]1.1715-1=0.1715[/tex]
convert to percentage
[tex]0.1715*100=17.15\%[/tex]
therefore
The price was increased by 17.15%
Answer: The price increased by 17.149618%.
Step-by-step explanation:
Given that the price of a certain item increases by 3.8% = 0.038 a total of 5 times.
So every time the price was (1 + 0.038) = 1.038 times the original price.
So after 5 times the price is = [tex]1.038^5=1.205[/tex] times the original price.
Then it decreased by 1.4% twice. So the new price is = [tex]1.205\cdot\left(1-0.014\right)^{2}=1.17149618[/tex] times the original price.
So the percentage increase is = [tex]\left(1.17149618-1\right)\cdot100 \%=17.149618 \%[/tex]
Learn more: https://brainly.com/question/12049968
I need help please ?!!!
Answer: B
Step-by-step explanation:
-19 + (-23)
Answer:
-19-23 is basically 19+23 but in the negatives.
so B is your answer
Step-by-step explanation:
what is the first need to solve (2/5) x -6=-16
Answer:
x = -25
Step-by-step explanation:
Solve for x:
(2 x)/5 - 6 = -16
Hint: | Put the fractions in (2 x)/5 - 6 over a common denominator.
Put each term in (2 x)/5 - 6 over the common denominator 5: (2 x)/5 - 6 = (2 x)/5 - 30/5:
(2 x)/5 - 30/5 = -16
Hint: | Combine (2 x)/5 - 30/5 into a single fraction.
(2 x)/5 - 30/5 = (2 x - 30)/5:
(2 x - 30)/5 = -16
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of (2 x - 30)/5 = -16 by 5:
(5 (2 x - 30))/5 = -16×5
Hint: | Cancel common terms in the numerator and denominator of (5 (2 x - 30))/5.
(5 (2 x - 30))/5 = 5/5×(2 x - 30) = 2 x - 30:
2 x - 30 = -16×5
Hint: | Multiply 5 and -16 together.
5 (-16) = -80:
2 x - 30 = -80
Hint: | Isolate terms with x to the left hand side.
Add 30 to both sides:
2 x + (30 - 30) = 30 - 80
Hint: | Look for the difference of two identical terms.
30 - 30 = 0:
2 x = 30 - 80
Hint: | Evaluate 30 - 80.
30 - 80 = -50:
2 x = -50
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of 2 x = -50 by 2:
(2 x)/2 = (-50)/2
Hint: | Any nonzero number divided by itself is one.
2/2 = 1:
x = (-50)/2
Hint: | Reduce (-50)/2 to lowest terms. Start by finding the GCD of -50 and 2.
The gcd of -50 and 2 is 2, so (-50)/2 = (2 (-25))/(2×1) = 2/2×-25 = -25:
Answer: x = -25
Answer:
x = -25
Step-by-step explanation:
(2/5)x - 6= -16 (add 6 to both sides)
(2/5) x = -16 + 6
(2/5) x = -10 (multiply both sides by 5)
2x = -10 (5)
2x = -50 (divide both sides by 2)
x = -50 / 2
x = -25